Traditional Korean Medical Treatment for Dizziness and Gait Instability due to Cerebellar Infarction: A Case Report - You Jung Lee; Jae Eun Jeong; Yeon Ah Choi; Jang Mi Park; Seung Min Lee; Eun Yong Lee; Cham Kyul Lee; Na Young Jo; Jeong Du Roh (MEDrang Inc., 2020)
This case study reports the effect of Korean medicine treatments on a 73 year-old female who had a cerebellar infarction. She was hospitalized for 120 days (without visiting Western medicine hospital) where she was treated with acupuncture, herbal decoction, pharmacopuncture, chuna, moxibustion and physiotherapy. Following treatment, her symptoms of dizziness were evaluated using the numeric rating scale and showed pain had reduced (3 to 0). The K-Modified Barthel, showed that life performance had improved (15 to 74), and the Berg balance scale showed an improved balance (2 to 32). Steps per minute and gait posture at stance phase for ataxia also showed improvement. This case report shows that Korean medicine treatment is effective in alleviating dizziness and improved gait instability caused by cerebellar infarction.